Text book of veterinary medicine, Volume 3 (of 5) - Law, James, 1838-1921 (Salt Lake City, UT : Project Gutenberg, 2023)
"Text Book of Veterinary Medicine, Volume 3" by James Law is a scientific publication written in the early 20th century. The text covers various diseases affecting animals, particularly focusing on the nervous system, genito-urinary organs, eyes, skin, and constitutional diseases. This volume seeks to provide veterinarians with detailed knowledge and diagnostic tools for a wide range of conditions that affect domestic and agricultural animals. The opening of the book introduces the fundamental concepts of veterinary medicine pertaining to nervous system diseases, emphasizing the interplay between the nervous system and bodily functions. It outlines how disorders can manifest through sensory and motor symptoms while discussing the importance of observing objective symptoms in animals, a challenge given the limitations of their ability to communicate. Additionally, it touches on the subtleties of diagnosing and understanding various conditions$1 (Bincluding their causes and treatment$1 (Bsignifying the importance of thorough observation and interpretation in veterinary practice. (This is an automatically generated summary.)s
Release date is 2023-12-28
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Veterinary medicine